MENINGKATKAN PRESTASI BELAJAR PAI DENGAN PEMBELAJARAN MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) - yakub yakub (MEDIA DIDAKTIKA, 2020)
The learning activities together can help stimulate active learning. Teaching and learning in the classroom is to stimulate active learning, but the ability to teach through the activities of a small group of co-operation will enable to promote active learning activities in a special way. What was discussed student with his friends and what it teaches students to his friends to enable them to gain an understanding and mastery of the subject matter. This study uses action research (action research) three rounds. each round consists of four stages: design, activities and observations, reflections, and refisi. Goal of this research is a class XI student Ak-1 of the school year 2014/2015. The data obtained as the result of formative tests, observation sheet teaching and learning activities. From the analysis we found that student achievement has increased from the first cycle to the third cycle, the first cycle (68.42%), the second cycle (81.58%), the third cycle (94.74%). The conclusions of this study is a cooperative learning can be a positive influence on students' achievement and motivation of Class XI Ak-1, and this model can be used as an alternative learning PAI.